1988
DOI: 10.1152/ajpgi.1988.254.3.g450
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of food intake and hepatic protein synthesis by recombinant-derived cytokines

Abstract: During inflammation, activated monocytes and lymphocytes synthesize and release many soluble protein mediators, such as interleukin (IL) 1, tumor necrosis factor-alpha, and IL-2. It is presently unclear which cytokines, if any, contribute to the anorexia and hepatic protein changes frequently seen during inflammation. To evaluate their potential role, food intake and liver and plasma protein synthesis were determined in both endotoxin-sensitive C57Bl/6j mice and endotoxin-resistant C3H/HeJ mice given either cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
1
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 0 publications
4
66
1
3
Order By: Relevance
“…33,34 However, neutralization of IL-1 by antibodies, 35 administration of an IL-1 receptor antagonist, 36 and transfection of an IL-1 receptor antagonist 37 failed to prevent cachexia in mice. The objectives of the current study were to determine the levels of TNF␣, IL-1␤, IL-6, and IL-8 in patients with CaP and to determine whether higher levels of these cytokines are associated with cachexia.…”
mentioning
confidence: 99%
“…33,34 However, neutralization of IL-1 by antibodies, 35 administration of an IL-1 receptor antagonist, 36 and transfection of an IL-1 receptor antagonist 37 failed to prevent cachexia in mice. The objectives of the current study were to determine the levels of TNF␣, IL-1␤, IL-6, and IL-8 in patients with CaP and to determine whether higher levels of these cytokines are associated with cachexia.…”
mentioning
confidence: 99%
“…A number of studies have been conducted to explore the factors responsible for this cachexia, and it has been revealed that elevated blood levels of tumour necrosis factor α (TNF-α), interleukin 1 (II-1), IL-6, IL-11, γ-interferon, leukaemia inhibitory factor or 24 kDa proteoglycan may induce cachexia (Beutler et al, 1986;Moldawer et al, 1988;Metcalf et al, 1990;Matthys et al, 1991;Strassmann et al, 1992a;Ohsumi et al, 1994;Todorov et al, 1996). One of these factors, IL-6, is a pleiotropic cytokine physiologically involved in the differentiation of myeloid and neuronal cells, and pathologically involved in the early host response to infection and injury (Kishimoto, 1989), in the proliferation of myeloma (Kawano et al, 1988), urological cancer cells (Miki et al, 1989;Okamoto et al, 1997a,b) and possibly breast cancer cells (Chiu et al, 1996), and in the development of hypercalcaemia and osteolytic metastases (De La Mata et al, 1995).…”
mentioning
confidence: 99%
“…111 The that accompanies acute inflammation. Not only are antianabolic properties of IL-1 and IL-6 could thus these cytokines catabolic when administered in vivo to be mediated in part through alterations in the IGF-1 animals, 40,65,97,102 but blocking an IL-1 or IL-6 response pathway. after a turpentine abscess reduces the carcass protein Similarly, in rats treated with RU38486 and TNFlosses that occur.…”
Section: Regulation Of Skeletal Muscle Protein In Cachexiamentioning
confidence: 99%
“…25 In fact, the majority of increases in whole body protein synthesis to healthy animals can reproduce the acute phase responses observed in acute inflammation. 28,40 This could be explained by increases in liver protein synthesis. Moreover, the livers of these animals were apoverlapping biological response is due in part to the fact that under in vivo conditions, TNF-a can induce proximately 10 -20% larger with 10 -20% more protein than the livers of comparably fasted animals.…”
mentioning
confidence: 99%
See 1 more Smart Citation